Pengaruh Metode Interval Menggunakan Kattlebell Terhadap Teknik Bantingan Pada Cabang Olahraga Pencak Silat - Shara Nur Aisyah; Mulyana Mulyana; Bambang Erawan (Jurnal Kepelatihan Olahraga, 2022)
The problems raised regarding improving kick techniques in pencak silat can be done with various forms of exercise, one form of exercise in this study is interval training using kettlebells. To find out the extent of the role of exercise, the researcher used an experimental method with a pre-experimental approach. The population in this study were 15 athletes from the POPSI Bhayu Manunggal hermitage, Bandung, West Java. The number of samples was 15 athletes and the technique used was purposive sampling. This research instrument uses a basic ability measurement test (MFS) of the pencak silat kickback technique developed by Johansyah Lubis. The results of research on the effect of interval training using kettlebells on back, hip, and leg slamming techniques, it can be concluded that there is a significant effect. Overall, the results of the initial and final tests experienced significant (meaningful) changes in the results of the pencak silat kickbacks. Then to find out the effect of differences in interval training methods by using kettlebells on the technique of slamming in the sport of pencak silat there is a significant difference in point scores between the initial test and the final test on each component of the slam. Based on the results of the study that the final test is higher than the initial test so it can be concluded that there is an average difference between the study subjects.